Helminths detection with video capsule endoscopy - A O Akopova (Терапевтический архив, 2019)
The article describes clinical observations of helminthiasis detection in 18 of 208 patients during video capsule endoscopy (VCE). Indications for the appointment of VCE were complex clinical situations associated with the search for inflammatory diseases of the small intestine and sources of small intestine bleeding. Because of the high cost of VCE the diagnosis of parasitic diseases should be based on laboratory techniques in clinical practice. Only in case of anemia of unknown etiology VCE demonstrates high efficiency.